TREVO stent-retriever mechanical thrombectomy for acute ischemic stroke secondary to large vessel occlusion registry. (29th September 2017) - Zaidat, Osama O; Castonguay, Alicia C; Nogueira, Raul G; Haussen, Diogo C; English, Joey D; Satti, Sudhakar R; Chen, Jennifer; Farid, Hamed; Borders, Candace; Veznedaroglu, Erol; Binning, Mandy J; Puri, Ajit; et al.
Abstract : Background: Recent randomized clinical trials (RCTs) demonstrated the efficacy of mechanical thrombectomy using stent-retrievers in patients with acute ischemic stroke (AIS) with large vessel occlusions; however, it remains unclear if these results translate to a real-world setting. The TREVO Stent-Retriever Acute Stroke (TRACK) multicenter Registry aimed to evaluate the use of the Trevo device in everyday clinical practice. Methods: Twenty-three centers enrolled consecutive AIS patients treated from March 2013 through August 2015 with the Trevo device. The primary outcome was deﬁned as achieving a Thrombolysis in Cerebral Infarction (TICI) score of ≥2b. Secondary outcomes included 90-day modified Rankin Scale (mRS), mortality, and symptomatic intracranial hemorrhage (sICH). Results: A total of 634patients were included. Mean age was 66.1±14.8 years and mean baseline NIH Stroke Scale (NIHSS) score was 17.4±6.7; 86.7% had an anterior circulation occlusion. Mean time from symptom onset to puncture and time to revascularization were 363.1±264.5 min and 78.8±49.6 min, respectively. 80.3% achieved TICI ≥2b. 90-day mRS ≤2 was achieved in 47.9%, compared with 51.4% when restricting the analysis to the anterior circulation and within 6 hours (similar to recent AHA/ASA guidelines), and 54.3% for those who achieved complete revascularization. The 90-day mortality rate was 19.8%. Independent predictors of clinical outcome included age, baseline NIHSS, use of balloon guide catheter, revascularization, and sICH. Conclusion: The TRACK Registry results demonstrate the generalizability of the recent thrombectomy RCTs in real-world clinical practice. No differences in clinical and angiographic outcomes were shown between patients treated within the AHA/ASA guidelines and those treated outside the recommendations.